Community-Based Correction (CBC): Efforts to Achieve a Balance Between Rehabilitation and Social Justice - Hamja Hamja (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
The criminal justice system in Indonesia has long played an important role in shaping societal norms and values, preventing crime, and ensuring public safety, thus fostering a secure and conducive environment. The concept of Community-Based Correction (CBC) has emerged as a progressive alternative that emphasizes a balance between rehabilitation principles and social justice. The purpose of this study is to analyze philosophical aspects, including reintegration and rehabilitation, restorative justice practices, community involvement and support, as well as the challenges and ethical considerations of community-based correction. The method used in this study is a normative juridical approach with philosophical analysis. The research concludes that the philosophy of community-based correction offers a glimmer of hope in the evolving criminal justice landscape. It emphasizes reintegration, rehabilitation, and restorative justice, challenging the punitive model as a comprehensive preventive solution. As society grapples with the complexities of criminal justice, community-based correction presents a promising way forward—an approach aimed not only at rehabilitating offenders but also healing communities and addressing systemic inequalities, ultimately creating a safer and fairer society.